IDENTIFICATION OF MORPHOLOGICAL CHARACTERISTICS OF LOCAL DURIAN KERINCI (Durio zibethinus.sp) - Jasminarni, Jasminarni; Evita, Evita; Novita, Trias (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The durian plant (Durio zibethinus Murr.) is known as a wet tropical fruit native to Indonesia. The durian plant is a native Indonesian fruit with uneven production throughout the year. Nationally, durian plants experience harvest seasons that are not simultaneous. Durian is very popular with everyone, so that some call it the king of fruits or the queen of fruits. Besides the fruit being sweet, fragrant with yellowish-white flesh color and rich in calories, vitamins, fat and protein, the stems can also be used as a building material. This study used participatory observation methods and in-depth interviews to obtain qualitative descriptive data with village officials, village communities and durian farmers in the Sitinjau Laut sub-district, Keliling Danau sub-district and Danau Kerinci sub-district. Based on research results, there are still many types of local superior durian plants in the community and need to be rescued because their number and whereabouts are difficult to track down and are very few and old. Types of durian in Kerinci Regency are very diverse in shape and type, each of which has advantages and disadvantages. There are still many types of superior durian with superior properties that are not inferior to other types of regional durian. The type of durian that has been recorded is a superior type that is already rare because there are very few of them.